Biologically effective dose of bromoxynil applied alone and mixed with metribuzin for the control of glyphosate-resistant horseweed in soybean. (2nd October 2021) - Westerveld, David B.; Soltani, Nader; Hooker, David C.; Robinson, Darren E.; Sikkema, Peter H.
Abstract: Glyphosate-resistant (GR) horseweed was first confirmed in Ontario in 2010. GR horseweed interference can reduce soybean yield by up to 97%. Bromoxynil is a photosystem II–inhibiting herbicide that is primarily used for annual broadleaf weed control in monocot crops. The objective of this study was to determine the biologically effective dose (BED) of bromoxynil applied alone and when mixed with metribuzin applied preplant for control of GR horseweed in soybean in Ontario. Five field experiments were conducted over a 2-yr period (2019–2020) to determine the predicted dose of bromoxynil with or without metribuzin that would control GR horseweed 50%, 80%, and 95%. No soybean injury was observed. The predicted doses of bromoxynil to achieve 50% and 80% control of GR horseweed were 98 and 277 g ai ha −1, respectively, at 8 wk after application (WAA). When mixed with metribuzin (400 g ai ha −1 ), the predicted doses of bromoxynil for 50%, 80%, and 95% control of GR horseweed were 10, 25, and 54 g ai ha −1, respectively. Bromoxynil (280 g ai ha −1 ) plus metribuzin (400 g ai ha −1 ) controlled GR horseweed 97%, a finding that was similar to the industry standards of saflufenacil + metribuzin (99% control) and glyphosate/dicamba + saflufenacil (100% control) at 8 WAA. This study concludes that bromoxynil + metribuzin applied before planting provides excellent control of GR horseweed in soybean.